Effectiveness of Disaster Education and Simulation on Adolescents' Perception and Preparedness - Budhiana, Johan; Dewi, Rosliana; Huda, Akhmad; Hasibuan, Sofyan Hadi (Media Karya Kesehatan, 2025)
Lack of experience, skills and related knowledge will put adolescents in a panic situation when faced with a disaster so that it will complicate the process of overcoming and rehabilitation that must be carried out. This activity aims to determine the effectiveness of education and simulation on the perception and preparedness of earthquakes in adolescents. The research method used quasi-experimental with One Group Pre-Test Post-Test Design. The population was all students at SMK Mutiara Terpadu Kabupaten Sukabumi with a sample of 40 respondents using the dropout formula, data collection using a questionnaire. The research instrument on perception and preparedness variables refers to the Likert scale and is declared valid and reliable. Data analysis used paired sample t-test. The results showed that there was an effect of education and simulation in improving adolescents' earthquake perception and preparedness with a p-value <0.05 and Cohen's d for perception = 3.25; and for preparedness = 2.1, the effect size indicated a large effect. It can be concluded that disaster education and simulation are effective in improving adolescents' perception and preparedness. Keywords: Earthquake, education, perception, preparedness, simulation.